Optimasi Kinerja Internet Dengan Implementasi Metode Peer Connection Queue (PCQ) Untuk Manajemen Bandwidth di Yayasan Bina Darma - Munda Tangkelangi, Fito (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to improve the efficiency of internet network performance at Bina Darma Foundation, which is experiencing request time out constraints due to non-optimal bandwidth usage, because there is no proper bandwidth management mechanism. The focus of the research is the application of the Peer Connection Queue (PCQ) method for automatic bandwidth distribution to all clients, combined with Simple Queue to provide max-limit and limit_at on each interface. Network performance evaluation is carried out before and after the application of the method, by paying attention to QoS parameters (throughput, delay, jitter, packet loss) and download/upload speed. From both combinations of methods, the results of this study show the success of the method in significantly improving network quality. Although there were changes in the QoS parameter values on some interfaces due to bandwidth limitation, the network quality category did not change. In fact, there was an improvement from "Good" to "Excellent" category in some cases. Although there were variations in download and upload speeds due to bandwidth allocation, the overall network quality remained "Excellent" based on the QoS parameters.